Tryptophol Coating Reduces Catheter-Related Cerebral and Pulmonary Infections by Scedosporium apiospermum - Kitisin T; Muangkaew W; Ampawong S; Sukphopetch P (Infection and Drug Resistance, 2020)
Thitinan Kitisin,1 Watcharamat Muangkaew,1 Sumate Ampawong,2 Passanesh Sukphopetch1 1Department of Microbiology and Immunology, Faculty of Tropical Medicine, Mahidol University, Bangkok, Thailand; 2Department of Tropical Pathology, Faculty of Tropical Medicine, Mahidol University, Bangkok, ThailandCorrespondence: Passanesh Sukphopetch Email natthanej.lup@mahidol.ac.thIntroduction: Central venous catheter (CVC) is a medical device that is used to administer medication for a long duration. Colonization by an emerging opportunistic pathogen Scedosporium apiospermum in the CVC lumen is frequently reported to cause severe complications in patients. Here, we describe the effect of fungal quorum-sensing molecule (QSM) known as tryptophol (TOH) to control S. apiospermum colonization in catheter tube lumens in both in vitro and in vivo models.Methods: Antifungal susceptibility of TOH against S. apiospermum was compared with voriconazole, and the colony diameter was determined on days 2, 4, and 6. Experimental catheterization rat model was conducted with pre-coating of TOH and voriconazole or an uncoated control and an infection with S. apiospermum. Biofilm formation on the catheter luminal surface was assessed using the scanning electron microscopy, crystal violet, and 2,3-bis(2-methoxy-4-ni-tro-5-sulfophenyl)-5-(phenylamino)-carbonyl-2H-tetra-zolium hydroxide (XTT) reduction assays. Brain and lung samples of catheterized rats were histopathologically assessed. Serum samples from catheterized rats were injected into Galleria mellonella larvae. Survival of catheterized rats and G. mellonella was determined.Results: TOH impeded the growth of S. apiospermum by reducing the colony diameter in a dose-dependent manner. TOH coating remarkably lessened S. apiospermum biofilm formation and fungal cell viability on the catheter luminal surface. Additionally, TOH coating lessens cerebral edema that is associated with abscess and invasive pulmonary damages due to S. apiospermum catheter-related infection. Furthermore, TOH coating also lessened the virulence of S. apiospermum in sera of experimental catheterized rats and extended the survival rate of larvae Galleria mellonella infection model.Conclusion: An alternative modification of catheter by coating with TOH is effective in preventing S. apiospermum colonization in vivo. Our study gives a new strategy to control catheter contamination and prevents nosocomial diseases due to S. apiospermum infection.Keywords: Scedosporium apiospermum, central venous catheter, quorum-sensing molecules, tryptophol, fungal biofilms, antifungal susceptibility, scedosporiosis, Galleria mellonella